The Role of Subregions in Modelling Regional Competitiveness — a Case Study of the West Subregion in Śląskie Voivodship - Tomasz Pilewicz (Barometr Regionalny)
The article elaborates on the role and possible actions to be taken by subregions in order to influence regional competitiveness. The objective of the article is to find the answer to the question of how the subregions defined as associations of smaller territorial units can contribute to investment competitiveness at a larger, regional level. Desk research and literature review analysis of the West Subregion in Poland shows that subregions can not only effectively support development of territorial units, which they embrace, but also contribute to the development of bigger territorial units, like a voivodship. Taking into account the fact that subregions in mature and complex organizational form, as in the example of the West Subregion, are a relatively rare phenomena in Poland, they provide a tapestry of good practices to follow. With relatively small operational costs the subregions’ role in providing information, lobbying for development issues, stimulation of local engagement and providing training, strategic management and cooperation development, is an example of modelling regional competitiveness based on the model of the region acting as an entrepreneurial organization.